1980
DOI: 10.1007/bf01315213
|View full text |Cite
|
Sign up to set email alerts
|

Villous damage induced by suction biopsy and by acute ethanol intake in normal human small intestine

Abstract: Previous studies by us indicated that ethanol in concentrations of 2.0-4.8% produced subepithelial blebs in the jejunum of the hamster. In the rat, due to rupture of the blebs, there was denudation of the villus tip epithelium. There are nos similar data on humans. Ethanol, in quantities equivalent to 4.8-6.4 ounces of 80 proof whiskey (diluted to 20% w/v), was infused into stomachs of 20 normal human volunteers. Subjects were divided into groups (Gr) according to the amount or type of alcohol given, and site … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

3
20
0
2

Year Published

1984
1984
2018
2018

Publication Types

Select...
5
4

Relationship

0
9

Authors

Journals

citations
Cited by 82 publications
(25 citation statements)
references
References 20 publications
3
20
0
2
Order By: Relevance
“…Either loss of the epithelial cells or disruption of the tight junctions will lead to an increase in intestinal permeability. Clinical studies demonstrated that acute alcohol administration can cause apparent histopathological changes in the proximal part of the small intestine, whereas chronic alcohol consumption only induces minor histopathological changes (9,12,34). Our previous study (30) also showed that intestinal histopathological alterations, such as loss of epithelial cells at the top of the intestinal villi, were associated with acute alcohol intoxication-induced intestinal barrier disruption in mice (30).…”
Section: Discussionmentioning
confidence: 81%
“…Either loss of the epithelial cells or disruption of the tight junctions will lead to an increase in intestinal permeability. Clinical studies demonstrated that acute alcohol administration can cause apparent histopathological changes in the proximal part of the small intestine, whereas chronic alcohol consumption only induces minor histopathological changes (9,12,34). Our previous study (30) also showed that intestinal histopathological alterations, such as loss of epithelial cells at the top of the intestinal villi, were associated with acute alcohol intoxication-induced intestinal barrier disruption in mice (30).…”
Section: Discussionmentioning
confidence: 81%
“…other studies were from several hours to several days following acute ethanol exposure (Worthington et al, 1978;Keshavarzian et al, 1994). It is imperative to examine tissue before repair has taken place, and clearly the intestine is capable of restoring both morphological alterations and decreases in barrier function during recovery from alcohol challenge (Millan et al, 1980;Tamai et al, 2000). Ileal intestine from mice treated acutely with ethanol in our study suffered gross morphological anomalies, where many intestinal villi had breaches in the epithelial layer.…”
Section: Discussionmentioning
confidence: 95%
“…Jak wykazały badania Millana i wsp. [66], po dożołądkowej aplikacji whisky rozcień-czonej do 20% lub wodnego roztworu etanolu o takim samym stężeniu w treści dwunastniczej stężenie alkoholu etylowego mieściło się w granicach 6,46-9,37 g/100 ml (8,2-11,9%), a w jelicie czczym 5,69-6,35 g/ 100 ml (7,2-8,0%). Stężenia te były wystarczająco duże do wywołania morfologicznego uszkodzenia kosmków jelitowych [66].…”
Section: Wpływ Napojów Alkoholowych Na Jelito Cienkieunclassified
“…[66], po dożołądkowej aplikacji whisky rozcień-czonej do 20% lub wodnego roztworu etanolu o takim samym stężeniu w treści dwunastniczej stężenie alkoholu etylowego mieściło się w granicach 6,46-9,37 g/100 ml (8,2-11,9%), a w jelicie czczym 5,69-6,35 g/ 100 ml (7,2-8,0%). Stężenia te były wystarczająco duże do wywołania morfologicznego uszkodzenia kosmków jelitowych [66]. W nowszych badaniach wykazano, że inkubacja komórek nabłonka jelitowego w roztworach etanolu w przedziale 5-10 g/100 ml skutkuje indukcją w nich apoptozy [67].…”
Section: Wpływ Napojów Alkoholowych Na Jelito Cienkieunclassified